Response and resistance to BRAFV600E inhibition in gliomas: Roadblocks ahead? - Capogiri, Monica; De Micheli, Andrea J.; Lassaletta, Alvaro; Muñoz, Denise P.; Coppé, Jean-Philippe; Mueller, Sabine; Guerreiro Stucklin, Ana S. (Frontiers in Oncology, 2023)
BRAFV600E represents the most common BRAF mutation in all human cancers. Among central nervous system (CNS) tumors, BRAFV600E is mostly found in pediatric low-grade gliomas (pLGG, 20%) and, less frequently, in pediatric high-grade gliomas (pHGG, 5-15%) and adult glioblastomas (GBM, 5%). The integration of BRAF inhibitors (BRAFi) in the treatment of patients with gliomas brought a paradigm shift to clinical care. However, not all patients benefit from treatment due to intrinsic or acquired resistance to BRAF inhibition. Defining predictors of response, as well as developing strategies to prevent resistance to BRAFi and overcome post-BRAFi tumor progression/rebound growth are some of the main challenges at present in the field. In this review, we outline current achievements and limitations of BRAF inhibition in gliomas, with a special focus on potential mechanisms of resistance. We discuss future directions of targeted therapy for BRAFV600E mutated gliomas, highlighting how insights into resistance to BRAFi could be leveraged to improve outcomes.